Parkinson's disease: convergence on synaptic homeostasis - Soukup, Sandra‐Fausia (EMBO J, 2018)
Parkinson's disease, the second most common neurodegenerative disorder, affects millions of people globally. There is no cure, and its prevalence will double by 2030. In recent years, numerous causative genes and risk factors for Parkinson's disease have been identified and more than half appear to function at the synapse. Subtle synaptic defects are thought to precede blunt neuronal death, but the mechanisms that are dysfunctional at synapses are only now being unraveled. Here, we review recent work and propose a model where different Parkinson proteins interact in a cell compartment‐specific manner at the synapse where these proteins regulate endocytosis and autophagy. While this field is only recently emerging, the work suggests that the loss of synaptic homeostasis may contribute to neurodegeneration and is a key player in Parkinson's disease.